A review of sarcoidosis etiology, diagnosis and treatment - Waly, Yahya Mostafa; Sharafeldin, Abu-Baker Khalid; Akhtar, Muhammad Umair; Chilmeran, Zaid; Fredericks, Salim (Frontiers in Medicine, 2025)
Sarcoidosis is an inflammatory disease characterized by the formation of granulomas in various organs, leading to inflammation and potential organ dysfunction. Symptoms often start with general signs like fatigue, fever, and weight loss, but vary depending on the affected organ. Diagnosis is challenging due to its diverse clinical presentation and lack of a definitive test, while treatment is complicated by the disease’s variable course, requiring a personalized approach. This review explores the role of genetic and environmental factors in sarcoidosis etiology, examines current challenges in diagnosis and treatment, and discusses how understanding etiology informs patient management and future treatment strategies.